The Role of Advocates in Providing Legal Assistance to the Community in the Perspective of Human Rights - Herning Setyowati; Nurul Muchiningtias (Universitas Negeri Semarang, 2018)
Legal assistance has a fairly important position in every criminal, civil, and state administrative justice system, no exception in Indonesia. The concept of legal assistance is related to a person's rights to carry out these rights, therefore legal assistance is carried out by legal experts and experienced people in order to carry out their profession. Legal assistance is carried out by the giver of legal assistance oriented to the values, namely the aspect of humanity to fight for human rights to live in a prosperous and just life.